National and Cultural Features of Taboo Names in the Turkic Languages (Eurasian Journal of Philology Science and Education, 2024)
The article is devoted to the analysis of peculiarities ofcustoms among the Turkic people, which have arisen in connection with various beliefs: an amulet-personal name, a protective name, an indirect name. Personal names with amulet and or "protective names" are an ancient custom of the Turkic people and a source of much interesting information. Generally, the taboo name, which arose in connection with the cult of the beast in the language of the Turkic people as a whole, has survived to this day as a relics. Particularly, the significance of the linguocultural definition of the taboo words, which characterize the historical ethnic trend, is highlighted. The taboo names of the Kazakh people, the custom of "at tergeu" (indirect names) are compared with other Turkic people. It was especially noticeable that the Siberian Turkic-speaking people use much more forbidden, that is, taboo names.The purpose of the article is to conduct a comparative study of the similarities and differences in the naming traditions of the Turkic people. In some Turkic languages ​​obtained for the study, common signs of anthropocomponents in the procedure for naming a child were revealed. Consideration of names in the material and ethno-cultural space makes it possible to determine the anthroponymic systems of the Turkic people.Key words: taboo, Turkic peoples, totem, custom, talisman, naming tradition, nickname